Multiobjetive optimum design of a two column radiator of central heating - Kowalski, Jerzy (Revista Técnica da Faculdade de Engenharia da de Zulia)
The paper describes the results of studies of the design model for a two-column radiator of central heating in tripleobjetive optimization conditions. The optimization problem is reduced to finding the minimum of a scales function in a 8-dimensional space bounded by 7, 8 or 9 inequality constraints. It is investigated the permissible region, and it is obtained an approximate shape of correspond1ng area in the objective space. A set of the polyoptimum solutions has been determined satisfying the optimization criterion. One selected afterwards the solutions preferred for design realization from this set.